Image segmentation using pulse coupled neural networks - Ranganath, H.S.; Kuntimad, G. (IEEE International Conference on Neural Networks, 1994, 1994)
It is shown that if the parameters of a pulse coupled neural network are properly adjusted neurons corresponding to the pixels of each region can be forced to pulse together. Each synchronous burst identifies an image region.< >